The Role of Balanced Scorecard to Raise the Financial Performance of SME’s Supply Chain - Khalid Hasan Al jasimee; Ghaith Hakim Malik; Hasan Talib Hashim (International Journal of Supply Chain Management, 2019)
Abstract- The purpose of this study is the role of the balanced scorecard to raise the financial performance of SMEs supply chain. This research is an applied and correlated study which formed the statistical society of the research staff with 1122 people for small and medium enterprises. Using the Cochran formula, the statistical sample of 286 was selected by stratified sampling. Using the Cochran formula, the statistical sample of 286 was selected by stratified sampling. The data gathering tool was a questionnaire of balanced scorecard and financially researcher-made questionnaire includes dimensions of value management, risk control and cost control. The reliability of the questionnaires was 0.79 for the human capital questionnaire and 0.80 for the financial performance questionnaire with Cronbach's alpha coefficient and the validity of the questionnaires was confirmed by experts. In this research, Pearson correlation coefficient and regression test were used. The results of the research showed that the scorecard is balanced and affects the financial performance of small and medium enterprises supply chain. In this research, Pearson correlation coefficient and regression test were used. The results of this study showed that the balanced scorecard is effective on the financial performance of small and medium enterprises supply chain. Keywords: Performance evaluation, Balanced Scorecard, Financial performance, Small and Medium Enterprises, Supply Chain.